2015
DOI: 10.21070/mid.v1i2.355
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berpengaruh Terhadap Pencapaian K4 Di Desa Sumberejo Wonoayu Sidoarjo

Abstract: Indonesia’s K4 coverage in 2014 was 86.85%, while the national target of K4 should reach 95%. This indicates that K4 coverage is still low. So it needsfurther research that aimed to analyze the factors influenced the achievement of K4 in the Sumberejo village Wonoayu Sidoarjo.This study was designed using retrospective analytic survey with cross sectional approach. The populationswere all mothers who had given birth in Sumberejo village in January-December 2014 period as amount 42 people. The sampling was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…The results of the study in Table 4 also show that pregnant women who have a higher education level (20%) have conducted the K4 visits according to the standard. It is consistent with the theory of Notoatmodjo (2010) and Cholifah and Putri (2016) regarding the level of education that it influences pregnant women in conducting antenatal care visits. However, pregnant women with a low education level also have done K4 visits according to the standard with a fairly large percentage of 53.3%.…”
Section: The Correla On Between Parity and K4 Visitssupporting
confidence: 90%
See 3 more Smart Citations
“…The results of the study in Table 4 also show that pregnant women who have a higher education level (20%) have conducted the K4 visits according to the standard. It is consistent with the theory of Notoatmodjo (2010) and Cholifah and Putri (2016) regarding the level of education that it influences pregnant women in conducting antenatal care visits. However, pregnant women with a low education level also have done K4 visits according to the standard with a fairly large percentage of 53.3%.…”
Section: The Correla On Between Parity and K4 Visitssupporting
confidence: 90%
“…Similar results were also stated in the studies of Cholifah and Putri (2016), Sarminah (2012) and Sari and INDRIANI (2014), which showed that there was no meaningful relationship between maternal employment and the regularity or completeness of antenatal care visit (K4). Research conducted by Onasoga et al (2012) in Nigeria also found that there was no relationship between maternal employment and visits to use ANC services during pregnancy.…”
Section: The Correla On Between Maternal Work Status and K4 Visitssupporting
confidence: 84%
See 2 more Smart Citations
“…Dukungan yang positif dari keluarga akan memberikan dampak yang positif terhadap kedatangan ibu ke tempat pelayanan kesehatan untuk memeriksakan kehamilan. Petugas kesehatan dapat memengaruhi ibu menjadi patuh dan efektif menggunakan anjuran sehingga dapat mengubah perilaku kesehatan ibu (Cholifah, 2015).…”
Section: Pendahuluanunclassified